The Effect of Return on Assets and Debt to Equity Ratio on Company Value (PT Samudera Indonesia, Tbk Study) - Angel Octaviana Harefa; Angel Lasmauli Marpaung; Ika Fitriani Panjaitan; Dian Putri Sihotang; Hamonangan Siallagan; Rizki Christian Sipayung (Universitas 17 Agustus 1945 Surabaya, 2023)
This study's goal is to determine how debt-to-equity ratios and partial returns on assets affect the firm value of PT Samudera Indonesia enterprises that are listed on the Indonesia Stock Exchange (IDX) in 2020–2022. Multiple linear regression analysis research methodologies are used in this quantitative type of investigation. Your hypothesis should be tested using a partial test (T test). For this study, quantitative data were employed, as well as data sources in the form of yearly financial reports for the companies published by PT Samudera Indonesia, Tbk via the Indonesia Stock Exchange (IDX) website. The study's conclusions show that the debt equity ratio and return on assets have a considerable negative impact on PT Samudera Indonesia, Tbk's company value. The SPSS program was used to determine the level of significance for each hypothesis test, which was beneficial for this study.